Risk Factors for Community-acquired Pneumonia among Children Under-five Years in Asia: A Systematic Review of Observational Studies - Muhammad Faza Soelaeman; Johan Cahyadirga (PT Kalbe Farma Tbk., 2023)
Background: Pneumonia is the leading cause of death among less than 5 year-old children worldwide, mainly in Asia in the form of community-acquired pneumonia. As primary prevention is considered crucial in combating the disease, risk factors need to be analyzed. Methods: Based on the PRISMA guidelines, observational studies were explored systematically by the PubMed MEDLINE database with inclusion and exclusion criteria. The studies retrieved are then assessed with the STROBE method. Results and Discussion: A total of 8 studies were included, with total participants of 16.862 children. STROBE score results range from 12.2 to 19.6. Several risk factors were associated with pneumonia and risk factor; the highest odds ratio are daytime abnormal behavior (OR: 11.06, 95% CI: 1.51-81.26, p=0.018), asthma diagnosis (OR: 5.85, 95% CI: 4.83–7.08), poor economic status (OR = 4.95, 95% CI: 2.38 to 10.28, p<0.05), and smoke-related cooking process (OR = 3.97, 95% CI: 2.00-7.88, p<0.05). Conclusion: The most associated host risk factor was health-related conditions while the most associated environmental risk factor was the smoke-related environment. Daytime abnormal behavior, the risk factor with the highest odds ratio. Latar Belakang: Pneumonia adalah penyebab kematian nomor satu pada anak usia di bawah 5 tahun di seluruh dunia, terutama di Asia, dalam bentuk community-acquired pneumonia. Pencegahan primer penyakit ini sangat penting; Oleh karena itu, perlu dilakukan analisis faktor risiko pneumonia pada anak usia di bawah 5 tahun. Metode: Berdasarkan pedoman PRISMA, tinjauan literatur untuk studi observasional dilakukan melalui database PubMed MEDLINE dengan kriteria inklusi dan eksklusi yang telah ditetapkan. Studi yang diperoleh dinilai menggunakan metode STROBE. Sebanyak 8 penelitian memenuhi kriteria dengan total subjek 16.862 anak. Hasil: Skor STROBE berkisar antara 12,2 hingga 19,6. Beberapa faktor risiko yang berhubungan dengan pneumonia; faktor risiko dengan odds ratio tertinggi adalah perilaku abnormal di siang hari (OR: 11,06; 95% CI: 1,51-81,26; p=0,018), asma (OR: 5,85; 95% CI: 4,83-7,08), status ekonomi buruk (OR=4,95; 95% CI: 2,38-10,28; p<0,05), dan proses memasak yang menghasilkan asap (OR=3,97; 95% CI: 2,00-7,88; p<0,05). Simpulan: Faktor risiko yang paling banyak dikaitkan adalah kondisi kesehatan subjek, sedangkan faktor risiko lingkungan yang paling banyak dibahas adalah lingkungan yang berhubungan dengan asap. Perilaku abnormal di siang hari yang merupakan faktor risiko dengan odds ratio tertinggi.